REINTERPRETASI AYAT JILBAB DAN CADAR: STUDI ANALISIS MA’NA CUM MAGHZA ATAS Q.S AL-AHZAB AYAT 59 DAN Q.S AN-NUR AYAT 31 - Ziska Yanti (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2022)
Hijab and veil are clothes that become the identity of Muslim women, the verses used are interpreted by various commentators. By consensus, scholars agree that the hijab is obligatory, although there is no agreement on what the hijab should cover. Some scholars say that the hijab must cover the entire body except the face and palms, some say that the hijab must cover the entire body including the face except for the one eye. For this reason, it is necessary to reinterpret the verses of the veil and the veil of the analysis study of ma'na cum maghza on QS. Al-Ahzab: 59 and QS: an-Nur: 31, this research will answer the meaning, understanding and implications of the hijab verse. Through the ma'na cum maghza approach, it can be concluded that the hijab is something that is obligatory which is not affected in the cultural context, in contrast to the veil whose laws are in accordance with the cultural context. However, the veil should not be banned in areas that do not recommend it because it is in accordance with human rights.